1999
DOI: 10.1121/1.424769
|View full text |Cite
|
Sign up to set email alerts
|

Optimal amplitude shading for arrays of irregularly spaced or non-coplanar elements

Abstract: The majority of optimal amplitude shading methods for arrays of irregularly spaced or non-coplanar elements rely on numerical optimizations and iterative techniques to compute the desired weighting function because analytic solutions generally do not exist. Optimality is meant here in the Dolph–Chebyshev sense to provide the narrowest mainlobe width for a given sidelobe level. A simpler and more efficient technique to compute the shading weights for arbitrary line array shapes or element spacings is presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The processing scheme that we have developed for the TVSS acoustic data is designed for conformal arrays and includes quadrature sampling, resampled amplitude shading, element-pattern compensation, and broadside beamforming on phase-compensated, overlapping subarrays with asymmetric projected element spacings. 23 This procedure permits split aperture processing of the beamformed output, which is performed because the processed data also were used to study acoustic backscatter from the ocean boundaries, and the phase zero-crossing of the output phasor is the most accurate means to detect the arrival time of boundary reflections on the maximum response axis of the beam. 24,25 For each ping, the split aperture process is used to form a phasor P(,t) for a given beam direction and time sample t every 3 degrees for directions spanning the 360 degrees around the TVSS axis.…”
Section: Processing Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The processing scheme that we have developed for the TVSS acoustic data is designed for conformal arrays and includes quadrature sampling, resampled amplitude shading, element-pattern compensation, and broadside beamforming on phase-compensated, overlapping subarrays with asymmetric projected element spacings. 23 This procedure permits split aperture processing of the beamformed output, which is performed because the processed data also were used to study acoustic backscatter from the ocean boundaries, and the phase zero-crossing of the output phasor is the most accurate means to detect the arrival time of boundary reflections on the maximum response axis of the beam. 24,25 For each ping, the split aperture process is used to form a phasor P(,t) for a given beam direction and time sample t every 3 degrees for directions spanning the 360 degrees around the TVSS axis.…”
Section: Processing Methodsmentioning
confidence: 99%
“…We used these response patterns because they successfully removed pointing errors which were observed in previous beamforming efforts with the TVSS. 23 Computer simulations, which used the TVSS transmit pattern and towfish attitude data for each run, indicated that the TVSS array beampatterns produced a maximum bias error of Ϫ7 dB and a maximum random error of Ϯ3.3 dB in the TVSS data. After echo-integrating and averaging over successive pings, these values were reduced to approximately Ϫ5 dB for the bias error and Ϯ1 dB for the random error.…”
Section: E System-related Sources Of Errormentioning
confidence: 99%
See 1 more Smart Citation